Optimasi Pemasaran UMKM di Dusun Kalirase, Trimulyo, Sleman - Al Azhar, Hafizh; Fitrianingsih, Ihtiara (JRCE (Journal of Research on Community Engagement), 2024)
Dusun Kalirase is a region within Trimulyo Village, Sleman District, where the majority of residents are engaged in agriculture and plantations. Additionally, there exist several Micro, Small, and Medium Enterprises (MSMEs) - UMKM in Indonesian language - with significant potential, having yet to be optimally managed, particularly in terms of marketing. This community service initiative aims to address several major challenges faced by MSMEs in Dusun Kalirase, such as a lack of knowledge about digital marketing, non-strategic business locations, and insufficient promotional resources. Through the "Dusun Kalirase MSME Marketing Socialization: Gleaming and Accessible" program, the team conducted a series of activities, categorized in community development, including brand identity creation and design, digital marketing support via social media, and adding MSME locations to Google Maps. The results indicate increased brand awareness, product appeal, and market reach for MSMEs in Dusun Kalirase. This program successfully helped MSMEs gain greater recognition within the local community and boost product sales.